High Linearity and Symmetry Ferroelectric Artificial Neuromorphic Devices Based on Ultrathin Indium‐Tin‐Oxide Channels - Siwei Wang; Xuemeng Hu; Baifan Qian; Jiajie Yu; Zhenhai Li; Qingqing Sun; David Wei Zhang; Qingxuan Li; Lin Chen (Advanced Electronic Materials)
Abstract Because of the limitations of the von Neumann structure and transistor size scaling, it is important to find new materials to build ultra‐thin artificial synapse devices. Doped In2O3 has attracted a lot of research due to its excellent on/off ratio, high mobility, and large on‐state current. In this paper, an ultrathin Sn‐doped In2O3 (ITO) is used as a semiconductor channel, and ferroelectric material HZO is used as a gate stack to fabricate synaptic transistors. The device has a great on/off ratio ≈108 with a memory window of 1.73 V. The device successfully simulates the characteristics of the human brain. Besides, a conductance modulation by ferroelectric polarization illustrates linear potentiation and depression characteristics. The devices achieve good linearity of 0.45 for potential and 0.73 for depression and low asymmetry of 0.89. Based on the MNIST and sign language MNIST database, ITO FeFETs successfully recognize numbers and sign languages. This work demonstrates the potential of ITO in building high‐performance artificial synaptic devices.